Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1152/ajpregu.00331.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery combined with medical therapy versus intensive medical therapy or calorie restriction and weight loss on glycemic control in Zucker diabetic fatty rats

Abstract: Abegg K, Corteville C, Docherty NG, Boza C, Lutz TA, Muñoz R, le Roux CW. Effect of bariatric surgery combined with medical therapy versus intensive medical therapy or calorie restriction and weight loss on glycemic control in Zucker diabetic fatty rats. Am J Physiol Regul Integr Comp Physiol 308: R321-R329, 2015. First published December 24, 2014 doi:10.1152/ajpregu.00331.2014.-Bariatric surgery rapidly improves Type 2 diabetes mellitus (T2DM). Our objective was to profile and compare the extent and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 48 publications
4
19
3
Order By: Relevance
“…22 The ZDF rat, a genetically engineered rat model of obesity associated with insulin resistance, dyslipidemia, and other complications, has been chosen to assess the effect of RYGB in many previous studies. [15][16][17][18][19]23 In the present study, RYGB surgery obviously decreased endotoxemia-associated indices, plasma LPS concentrations, and serum and adipose tissue concentrations of the inflammatory cytokines TNF-α and IL-1β. Recently, the inflammatory reaction in insulin resistance, obesity, and T2D has attracted increasing attention.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…22 The ZDF rat, a genetically engineered rat model of obesity associated with insulin resistance, dyslipidemia, and other complications, has been chosen to assess the effect of RYGB in many previous studies. [15][16][17][18][19]23 In the present study, RYGB surgery obviously decreased endotoxemia-associated indices, plasma LPS concentrations, and serum and adipose tissue concentrations of the inflammatory cytokines TNF-α and IL-1β. Recently, the inflammatory reaction in insulin resistance, obesity, and T2D has attracted increasing attention.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, research on the mechanism by which RYGB relieves diabetes‐associated obesity is important . The ZDF rat, a genetically engineered rat model of obesity associated with insulin resistance, dyslipidemia, and other complications, has been chosen to assess the effect of RYGB in many previous studies . In the present study, RYGB surgery obviously decreased endotoxemia‐associated indices, plasma LPS concentrations, and serum and adipose tissue concentrations of the inflammatory cytokines TNF‐α and IL‐1β.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Among common bariatric procedures, Roux-en-Y gastric bypass (RYGB) surgery is considered the most effective procedure for producing long-term weight loss and metabolic improvement in obese patients. Glucose homeostasis has been reported to be improved prior to marked increases in weight loss and insulin sensitivity in both rodents and humans, particularly in the context of T2D [4,5], suggesting that the benefit effects of RYGB may not completely depend on food restriction and malabsorption. Previous studies have shown that RYGB promotes the secretion of incretins, such as glucagon-like peptide 1 (GLP-1), and improves the metabolic homeostasis [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%